DATA ENGINEERING FOR SCALABLE MACHINE LEARNING DESIGNING ROBUST PIPELINES - Chittaranjan Pradhan; Abhishek Trehan, (INTERNATIONAL JOURNAL OF COMPUTER ENGINEERING AND TECHNOLOGY (IJCET), 2024)
Machine learning (ML) applications are becoming more popular in data-driven businesses, which means that strong and scalable data engineering pipelines are a must. In order to prepare, analyse, and distribute high-quality data for ML models, these pipelines are crucial. The methods and best practices for building data engineering pipelines that are scalable and optimised for machine learning operations are discussed in this article. It identifies important problems like data velocity, diversity, and volume and offers solutions including distributed processing frameworks, automated processes, and cloud-native architectures. For the ML lifecycle to be both reliable and efficient, feature engineering, real-time data streaming, and pipeline monitoring must be integrated. In order to adapt to changing data and model needs, the research also stresses the need of pipeline architecture that is both reproducible and modular. In addition to improving model performance, the results show that robust pipelines shorten development periods and facilitate the widespread implementation of ML systems.The study finishes with some recommendations on how to construct scalable pipelines that meet the demands of contemporary machine learning. Data engineers are vital to the success of scaled machine learning because they build reliable pipelines for handling large data sets consistently and efficiently. Investigated in this study are the whys, whats, and hows of data engineering processes tailored to ML systems. Crucial components include data collection, processing, validation, storage, and engagement with ML frameworks. By placing an emphasis on automation, fault tolerance, and scalability, robust pipelines remove obstacles to processing massive volumes of data rapidly without compromising consistency or quality. The findings emphasise the value of distributed systems, stream processing, and orchestration tools for reaching performance goals. Additional issues covered in this article include data security, handling data schema changes, and integrating various data sources. Practical recommendations for constructing scalable pipelines in line with machine learning goals are provided to expedite model training, deployment, and inference. This study found that in today's data-driven environment, building scalable and effective machine learning solutions requires robust data engineering pipelines.